2018
DOI: 10.1186/s13660-018-1903-8
|View full text |Cite
|
Sign up to set email alerts
|

Blow-up analysis for a periodic two-component μ-Hunter–Saxton system

Abstract: The two-component μ-Hunter–Saxton system is considered in the spatially periodic setting. Firstly, two wave-breaking criteria are derived by employing the transport equation theory and the localization analysis method. Secondly, a sufficient condition of the blow-up solutions is established by using the classic method. The results obtained in this paper are new and different from those in previous works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hence, we can say 2-μHS system equation ( 4) lies in an intermediate between 2-CH and 2-HS systems. e Cauchy problem for equation (4) has been studied extensively in [24][25][26][27]. In addition, research studies have shown that this system is locally well-posed [26] for (u 0 , ρ 0 ) ∈ H s × H s− 1 , s > (3/2); besides, its global classical solutions [26] and finite-time blowup solutions [25,27] have also been found, and its geometric background has been comprehensively given by Escher in [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we can say 2-μHS system equation ( 4) lies in an intermediate between 2-CH and 2-HS systems. e Cauchy problem for equation (4) has been studied extensively in [24][25][26][27]. In addition, research studies have shown that this system is locally well-posed [26] for (u 0 , ρ 0 ) ∈ H s × H s− 1 , s > (3/2); besides, its global classical solutions [26] and finite-time blowup solutions [25,27] have also been found, and its geometric background has been comprehensively given by Escher in [24].…”
Section: Introductionmentioning
confidence: 99%
“…e Cauchy problem for equation (4) has been studied extensively in [24][25][26][27]. In addition, research studies have shown that this system is locally well-posed [26] for (u 0 , ρ 0 ) ∈ H s × H s− 1 , s > (3/2); besides, its global classical solutions [26] and finite-time blowup solutions [25,27] have also been found, and its geometric background has been comprehensively given by Escher in [24]. e global admissible weak solution of system equation (4) has been obtained in [28] by mollifying the initial date.…”
Section: Introductionmentioning
confidence: 99%